Simvastatin Enhanced Anti-tumor Effects of Bevacizumab against Lung Adenocarcinoma A549 Cells via Abating HIF-1α-Wnt/β-Catenin Signaling Pathway - Tu, Xin; Zhang, Jian; Yuan, Wei; Wu, Xia; Xu, Zhi; Qing, Cuo (Anti-Cancer Agents in Medicinal Chemistry, 2023)
Background: Bevacizumab increased hypoxia-inducible factor (HIF-1α) expression attenuates its antitumor effect. Simvastatin can reduce the expression of HIF-1α to exert a tumor-suppressive effect in many in vitro experiments. Therefore, this study aimed to determine whether simvastatin could strengthen the anti-tumor activity of bevacizumab in lung adenocarcinoma. Objective: To determine whether simvastatin could strengthen the anti-tumor activity of bevacizumab in lung adenocarcinoma. Methods: The changes in the biological behavior of A549 cells treated with different drugs were determined through colony forming assay, Cell Counting Assay-8 (CCK-8), transwell assay, wound healing assay, and flow cytometry. The expressions of pathway-related factors HIF-1α and β-Catenin were determined via qRT-PCR and western blotting. The expressions of proliferation-related proteins, invasion-related proteins, and apoptosis-related proteins were detected by western blotting. In addition, a xenograft non-small cell lung cancer model in nude mice was used to explore in vivo tumor growth. Results: We found that simvastatin combined with bevacizumab synergistically suppressed the proliferation, migration, and invasion of A549 cells while promoting their apoptosis. As demonstrated by qRT-PCR and western blotting experiments, the bevacizumab group displayed a higher expression of pathway-related factors HIF-1α and β-Catenin than the control groups, however simvastatin group showed the opposite trend. Its combination with bevacizumab induced elevation of HIF-1α and β-catenin expressions. During in vivo experiments, simvastatin inhibited tumor growth, and in comparison, the inhibitory effects of its combination with bevacizumab were stronger. Conclusion: Based on our findings, simvastatin may affect the biological responses of bevacizumab on A549 cells by restraining the HIF-1α-Wnt/β-catenin signaling pathway, thus representing a novel and effective combination therapy that can be potentially applied in a clinical therapy for lung adenocarcinoma.
Keywords: β-catenin